PRESENT AND FUTURE OUTCOME &CHALLENGES IN PHYSICAL EDUCATION & SPORTS - Dr. Gaganendu Dash1, Dr. Rajesh Kumar Dhaka2 (International journal of economic perspectives, 2019)
The aim of this paper is to identify the present and futureoutcome and challenges in physical education and sports and based on these current challenges, future trends and challenges would be discussed. There are various factors which are diminishing the interest of students in physical education activities. Although the physical education is being taught as a part of curriculum in all the schools but lack of adequate time and trained teachers, good facilities are responsible for little interest in this field. The future challenges to make this field interesting involves an adequate curriculum, sufficient funds allotment for holding various competitions and role of technology to create awareness about the importance of physical activities and sports in our daily life. All these issues have been discussed in the present study.